The relevance of water recirculation in large scale mineral processing plants with a remote water supply. (10th March 2018) - Ihle, Christian F.; Kracht, Willy
Abstract: Water and energy are essential requirements for mineral processing plants, and they can be either scarce or expensive. In the present paper, the implications of a remote water source location (typically the seashore) are analyzed in terms of a definition for the combined water and energy operational cost required to transport ore concentrate using long distance pipelines. A typical process route is defined to expose the relevance of key process variables, including source remoteness and water reclamation both from tailing storage facilities and thickeners. Both mass and energy balances have been made to give an estimation of specific energy consumptions for a typical large scale Chilean mineral processing operations, considering a number of realistic hydraulic design criteria to make a comparative analysis of different plant processing capacities. In the present cost function definition, an account has been made on whether the water is either makeup or has been recirculated on the plant, and a distinction has been made on whether tailings are conventional or thickened, which allowed to analyze the relevance of in-plant water recovery compared to water recovery from the tailing disposal site. This has allowed to express the cost of water in terms of the various energy cost terms, thus showing in this case that the cost of water is ultimately the cost of energy, and therefore all cost components become proportional to the unit cost of energy. A piecewise constant pipeline diameter analysis scheme has been defined to allow studying the implications of water recovery on widely different plant sizes. Results show that for fixed water recovery rates, increasing plant throughput tends to cause a decrease on the specific energy for water transport. On the other hand, for fixed pipeline diameters, increasing the throughput causes an increase on the specific energy consumption, but such increase rate becomes milder at higher throughput rates. This suggests the advantage of the existence of common makeup water supply systems for mining districts with more than one mineral processing plant. On the other hand, for constant pipeline diameters, increasing the water recovery from the tailing disposal site or from thickeners generates a decrease of water specific energy consumption, where in the case of the water recovery from the tailing disposal site such decrease rate becomes stronger with the amount of water recovered. Results also shows that, except for very high solid concentrations, water makeup costs dominate over recirculation ones, supporting that producing thickened tailings is a more efficient option than conventional ones in the sense of specific energy consumption, in spite of the additional energy costs due to slurry transport that this option implies. Highlights: Chilean mining operations face considerable water scarcity near their operations. Several mining companies supply water through long distance pipelines. Water and energy costs may be estimated in terms of unit energy costs solely. Enhanced in-plant recirculation may significantly reduce total makeup water costs.